Co-production of the quality of patient-centered outcomes research partnerships instrument for people with mental health conditions - Karen Fortuna; Amanda Myers; Jessica Brooks; Caroline Collins-Pisano; Skyla Marceau; Sarah Pratt; Kathy Lyons; Robert Walker; Shavon Thompson; Kaycie Greene; Willie Pringle; Katina Carter (The Beryl Institute, 2021)
Mounting scientific evidence over the past decades in the field of psychiatry has shown community engagement in research produces more relevant research, increased uptake of research findings, and better clinical outcomes. Despite the need for the integration of community engagement methodologies into the scientific method, doctoral and master's level competencies in the field of psychiatry commonly do not include dedicated training or coursework on community engagement methodologies. Without appropriate training or research experience, attempts to facilitate community engagement are often ineffective and burdensome and leave stakeholders feeling disenfranchised. The goal of this study was to co-produce an instrument designed to improve the quality of community engagement research practices by measuring the degree to which researchers have partnered with psychiatric patient stakeholders. The development of the Quality of Patient-Centered Outcomes Research Partnerships Instrument included an iterative co-production process with psychiatric patient stakeholders and scientists, including item formulation, followed by two phases of cognitive interviews with psychiatric patient stakeholders to assess and refine instrument items. A pilot study was conducted to assess acceptability and feasibility. The pilot study of the Patient-Centered Outcomes Research Partnerships Instrument suggested feasibility and acceptability among psychiatric patient stakeholders. The Quality of Patient-Centered Outcomes Research Partnerships Instrument may be a valuable tool to enhance the quality of community engagement research practices within the field of psychiatry. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens